A randomized, controlled, cross-over study of the safety and efficacy of superabsorbent diaper for babies with mild-to-moderate diaper rash (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Super-absorbent diaper is a disposable diaper with new technology which has a soft-airy structure, breathable sheet, and rich absorbent core. This study aimed to compare the safety and efficacy of super-absorbent diaper with standard absorbent diaper. METHODS A single-blinded, randomized, controlled, cross-over study was performed in 324 months babies. A safety study was performed in 113 babies without diaper rash (group A: super-absorbent to standard and B: standard to super-absorbent) and efficacy study in 59 babies with mild-to-moderate diaper rash (group C: super-absorbent to standard and D: standard to super-absorbent). Each group used super-absorbent or standard diaper for 2 weeks. Skin assessment scores (SAS) were recorded at baseline, week-2, and week-4. Non-parametric tests were used to analyze the data. RESULTS In the safety study, there was no significant increase of SAS in group A at week-2 and -4, but in group B there was a significant increase of SAS (1.9 to 4.1, p = 0.001) at week-2 with a significant reduction at week-4 (4.1 to 2.2, p<0.001). In the efficacy study, there was a reduction of SAS at week-2 in group C (p = 0.07) and D (p = 0.05). However, SAS increased in group C (6.4 to 8.3, p = 0.2) and decreased in group D (8.6 to 6.1, p = 0.13) at week-4. Super-absorbent diaper showed a significant reduction of SAS in the pubic areas (1.43 to 0.73, p<0.011). CONCLUSIONS The new super-absorbent diaper is safe to use and may have efficacy in the improvement of skin conditions and diaper rash, especially in the pubic areas.